Working On the Impossible: Early childhood policies in Namibia - Penn, Helen (Childhood (Copenhagen, Denmark), 2008)
This article discusses the complexities of aid-giving using the example of early childhood policies in Namibia. It supports a critical view of aid processes and of World Bank endeavours in particular. Using an analysis of the World Bank funded education sector-wide improvement plan (ETSIP) in Namibia and three Namibian local case studies, it shows how the local circumstances of young children and their parents are ignored in order to fit in with donor preconceptions, and how senior officials come to adopt those views. It argues that universally derived policies on early childhood development are misapplied, and poverty and inequality are ignored in the search for technocratic solutions.